Analisis Sinergitas Unsur Patroli Guna Penegakan Hukum dalam Rangka Mendukung Operasi Keamanan Laut di Alki Ii - Agung Rikwan Harjanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The security of the Indonesian maritime domain, particularly in the strategic ALKI II (Indonesian Archipelagic Sea Lanes II), requires synergy between patrol elements to enforce the law effectively. This maritime region serves as a crucial international shipping lane, necessitating a coordinated approach to security enforcement. Effective law enforcement in ALKI II depends on the seamless collaboration among various maritime security stakeholders, including the Navy, Marine Police, and related agencies. Each of these entities plays a significant role in safeguarding Indonesia's maritime sovereignty by preventing illegal activities such as smuggling, piracy, and illegal fishing. This study analyzes the level of synergy among these patrol units in supporting maritime security operations, focusing on operational coordination, resource sharing, and strategic policy alignment. Using a qualitative approach with data collected through structured interviews, field observations, and document analysis, this research identifies key challenges and opportunities in optimizing inter-agency cooperation. The findings suggest that enhanced inter-agency collaboration, the integration of advanced surveillance technologies, and the establishment of clear operational frameworks significantly improve the effectiveness of law enforcement in ALKI II. Additionally, the study highlights the necessity of standardized communication protocols and joint training programs to strengthen coordination among security agencies. The results provide actionable insights for policymakers in designing comprehensive maritime security strategies that align with national defense priorities.